Predictors of FabAV use in copperhead envenomation. (4th May 2022) - Ramirez-Cueva, Fatima; Larsen, Adam; Knowlton, Elise; Baab, Kelsey; Rainey Kiehl, Robin; Hendrix, Amy; Condren, Michelle; Woslager, Megan
Abstract: Context: Crotaline snake envenomation is a serious medical condition affecting thousands of Americans each year. Variation in the treatment of Crotaline snakebites exists among physicians in the United States. Management of copperhead snakebites is controversial with some experts advocating minimal intervention, rarely necessitating antivenom use and, even more rarely, surgical intervention. This study assessed the use of Crotaline Polyvalent Immune Fab antivenom (Ovine) (FabAV) and explored factors influencing the decision to prescribe antivenom for copperhead envenomation in patients in Northeastern Oklahoma. Methods: A retrospective cohort study examining electronic medical records of patients with copperhead snakebites from July 1, 2014 to August 31, 2019. Data collected included: patient demographics, transfer information, snake species, bite site, progression of local tissue effects, additional clinical and lab results, patient comorbidities, and treatment strategy. Associations between patient variables and treatment were evaluated using the chi-square test of independence, median test, and logistic regression analysis. Associations were statistically significant if p  < 0.05. Discussion: Of the 130 patients bitten by a copperhead, a majority (75%) received FabAV. Symptoms of copperhead envenomation were mostly limited to the progression of tissue damage. Predictors of treatment with FabAV included progression of venom effects across major joints, younger age, comorbidities, and upper extremity bites. Conclusions: Patients who have multiple comorbidities, upper extremity bites and progression of venom effects across major joints are more likely to be treated with FabAV. The high usage of FabAV at the study site underscores the need for continued work to optimize the use of antivenom for copperhead envenomations.